2022
DOI: 10.12659/msm.938926
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physiotherapy to Correct Rounded Shoulder Posture in 30 Patients During the COVID-19 Pandemic in South Korea Using a Telerehabilitation Exercise Program to Improve Posture, Physical Function, and Reduced Pain, with Evaluation of Patient Satisfaction

Abstract: This paper was supported by the Academic Research Fund of Dr. Myung Ki (MIKE) Hong in 2021 Conflict of interest: None declared Background:This study aimed to evaluate the effect of physiotherapy to correct rounded shoulder posture (RSP) in 30 patients during the COVID-19 pandemic in South Korea using telerehabilitation exercise programs to improve posture and physical function and reduce pain, with evaluation of patient satisfaction. Material/Methods:Thirty participants with RSP participated in this study for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
2
0
0
Order By: Relevance
“…Regarding postural alignment, our results showed that the craniovertebral, cranial, and shoulder angles significantly improved after six weeks of online respiratory and corrective exercises. Our findings are in line with those of previous studies suggesting that telerehabilitation exercises significantly improved postural deviation [ 31 33 ]. Thus far, many studies have evaluated the significant effects of different exercise programs, such as therapeutic exercises [ 34 ], scapular stabilization [ 35 ], and strengthening exercises [ 36 ] on the neck, shoulder, and head posture.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Regarding postural alignment, our results showed that the craniovertebral, cranial, and shoulder angles significantly improved after six weeks of online respiratory and corrective exercises. Our findings are in line with those of previous studies suggesting that telerehabilitation exercises significantly improved postural deviation [ 31 33 ]. Thus far, many studies have evaluated the significant effects of different exercise programs, such as therapeutic exercises [ 34 ], scapular stabilization [ 35 ], and strengthening exercises [ 36 ] on the neck, shoulder, and head posture.…”
Section: Discussionsupporting
confidence: 93%
“…In line with previous studies [ 46 , 47 ], our findings showed that prescribing respiratory and corrective exercises improved QOL in the study participants. It seems that the rehabilitation exercise program generally had favorable effects on QOL as the participants' perceptions of their QOL were improved by encouraging their physical and mental health, which is consistent with previous studies [ 31 , 33 , 42 , 48 , 49 ].…”
Section: Discussionsupporting
confidence: 89%
“…After reading the full text, we were left with 13 articles, of which two were also excluded. The work carried out by Lee et al [30] was excluded because both groups received telerehabilitation treatments. The studies by Hwang et al [22] were rejected because the variables of analysis were not of interest for the present work.…”
Section: Literature Search and Screeningmentioning
confidence: 99%